Detailed Multi‐dimensional Modeling of Direct Internal Reforming Solid Oxide Fuel Cells. Issue 3 (1st June 2016) - Tseronis, K.; Fragkopoulos, I.S.; Bonis, I.; Theodoropoulos, C.
Abstract: Fuel flexibility is a significant advantage of solid oxide fuel cells (SOFCs) and can be attributed to their high operating temperature. Here we consider a direct internal reforming solid oxide fuel cell setup in which a separate fuel reformer is not required. We construct a multidimensional, detailed model of a planar solid oxide fuel cell, where mass transport in the fuel channel is modeled using the Stefan‐Maxwell model, whereas the mass transport within the porous electrodes is simulated using the Dusty‐Gas model. The resulting highly nonlinear model is built into COMSOL Multiphysics, a commercial computational fluid dynamics software, and is validated against experimental data from the literature. A number of parametric studies is performed to obtain insights on the direct internal reforming solid oxide fuel cell system behavior and efficiency, to aid the design procedure. It is shown that internal reforming results in temperature drop close to the inlet and that the direct internal reforming solid oxide fuel cell performance can be enhanced by increasing the operating temperature. It is also observed that decreases in the inlet temperature result in smoother temperature profiles and in the formation of reduced thermal gradients. Furthermore, the direct internal reforming solid oxide fuel cell performance was found to be affected by the thickness of the electrochemically‐active anode catalyst layer, although not always substantially, due to the counter‐balancing behavior of the activation and ohmic overpotentials.